2002
DOI: 10.1046/j.1471-4159.2002.01021.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of nadrin variants, a novel family of GTPase activating protein for rho GTPases

Abstract: Nadrin is a GTPase-activating protein (GAP) for the rho family of GTPases that controls Ca 2+ -dependent exocytosis in nerve endings. In this study, three novel splice variants of nadrin were identified and the variants were designated as nadrin-102, -104, -116 and -126 according to their relative molecular masses. All nadrin variants share the GAP domain, coiled-coil domain, serine/threonine/proline-rich domain, SH3-binding motif, and a successive repeat of 29 glutamines. Tissue distribution analyses using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Because PACSIN proteins lack a RhoGAP domain we asked whether the presence of a GTPase-activating protein (GAP) may be required in the PACSIN 1-Rac1 complex to mediate Rac1 activity. A previous study identified NADRIN (also named RICH1) as a Rac1 GAP, which also interacts with the SH3 domain of PACSIN 1 (32,33). We confirmed the binding of PACSIN 1 to NADRIN (Fig.…”
Section: Pacsin 1 and Rac1 Act In A Complex-smallsupporting
confidence: 85%
“…Because PACSIN proteins lack a RhoGAP domain we asked whether the presence of a GTPase-activating protein (GAP) may be required in the PACSIN 1-Rac1 complex to mediate Rac1 activity. A previous study identified NADRIN (also named RICH1) as a Rac1 GAP, which also interacts with the SH3 domain of PACSIN 1 (32,33). We confirmed the binding of PACSIN 1 to NADRIN (Fig.…”
Section: Pacsin 1 and Rac1 Act In A Complex-smallsupporting
confidence: 85%
“…Transfected cells lost actin stress fibers, retracted from the coverslip, and extended long filopodia, ruffles, and lamellipodia. Such a destructive effect on the actin cytoskeleton has been shown for several RhoGAP proteins (11,12,48,53,55). One of the accepted explanations for this phenomenon is inactivation of Rho family GTPases by GAP proteins, based on the established physiological roles of Rho GTPases in the regulation of the actin cytoskeleton.…”
Section: Discussionmentioning
confidence: 97%
“…tion. For example, diffuse cytoplasmic localization has been reported for RICH-1 (25); ␤-chimaerin, ARHGAP4, and IQGAP are associated with the Golgi apparatus (45)(46)(47); IQGAP and nadrins have been observed in the nucleus (47,48); and ARH-GAP4 and PSGAP show perinuclear localization (46,49). Some RhoGAP proteins co-localize with different structures of the actin cytoskeleton, which is their primary cytoskeletal target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGF-induced Rac and Cdc42 activation and neurite formation may be further modulated by a specific splice variant of the RhoGAP Nadrin, Nadrin-116. Nadrin-116 inhibits NGF-induced neurite outgrowth in PC12 cells, which is dependent on Nadrin's GAP activity, suggesting a Rac-or Cdc42-directed preference for this molecule in relation to neurite formation (Furuta et al 2002).…”
Section: Rac and Cdc42 Signaling Pathways That Promote Neurite Formationmentioning
confidence: 97%